2010
DOI: 10.1021/pr100562w
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of hNek6 Interactome Reveals an Important Role for Its Short N-Terminal Domain and Colocalization with Proteins at the Centrosome

Abstract: Physical protein-protein interactions are fundamental to all biological processes and are organized in complex networks. One branch of the kinome network is the evolutionarily conserved NIMA-related serine/threonine kinases (Neks). Most of the 11 mammalian Neks studied so far are related to cell cycle regulation, and due to association with diverse human pathologies, Neks are promising chemotherapeutic targets. Human Nek6 was associated to carcinogenesis, but its interacting partners and signaling pathways rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(69 citation statements)
references
References 78 publications
5
64
0
Order By: Relevance
“…The protein bands were removed from the gel and were submitted to in-gel trypsin (20 ng/l), chymotrypsin (100 ng/l), and pepsin A (75 ng/l) digestion as described previously (19).…”
Section: Protein Digestionmentioning
confidence: 99%
“…The protein bands were removed from the gel and were submitted to in-gel trypsin (20 ng/l), chymotrypsin (100 ng/l), and pepsin A (75 ng/l) digestion as described previously (19).…”
Section: Protein Digestionmentioning
confidence: 99%
“…NEK6 and NEK7 notably lack a C-terminal domain. They consist solely of a kinase domain with a short N-terminal extension that might be important for substrate recognition (Vaz Meirelles et al, 2010). Indeed, the non-catalytic regions of the other NEKs almost certainly contribute to substrate recognition, as well as regulation, and this is illustrated, for example, by the recognition of NEK6 and NEK7 by a sequence in the C-terminus of NEK9 (Roig et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The NEK6 interactome as shown in Table 3 includes many genes putatively involved in immune signaling including IKBKB, DDX3X, ILF2, PRDX4, RHOC, S100A8, S100A9, and TOLLIP; however, none of these proteins act as direct NEK6 substrates in vitro in comparison to the potent substrates CK1α and YES1 (Supplemental Figure 6). In addition, NEK6 has previously been reported to interact with RELB (Vaz Meirelles et al, 2010) and increase the activity of an NFκB promoter (Matsuda et al, 2003), and it has also been previously reported to phosphorylate STAT3 (Jeon et al, 2010); however, RELA, RELB, STAT1, STAT3, and STAT5 are also not phosphorylated to an appreciable extent by NEK6 in our in vitro kinase assay. Thus, the impact of NEK6 on immune signaling may be indirect or the relevant substrate(s) have yet to be identified.…”
Section: Gene Expression Changes Mediated By Nek6 Substratesmentioning
confidence: 48%
“…However, there is little evidence from our unbiased studies suggesting any of these pathways as the predominant mechanism of NEK6-mediated castration resistance in our model. Previous proteomic work (Vaz Meirelles et al, 2010) identifies multiple interacting partners and substrates that implicate NEK6 in a variety of signaling pathways including cell cycle, cytoskeleton organization, DNA repair, Notch and NFκB pathways. In our studies, the gene expression signature mediated by NEK6 overexpression in the context of castration implicates differentiation and immune processes in conferring castration resistance to tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation